Clinical application of transcranial magnetic stimulation in multiple sclerosis - Xiaoliang Zhou; Xiaoliang Zhou; Kailin Li; Kailin Li; Si Chen; Si Chen; Wenbin Zhou; Wenbin Zhou; Jing Li; Jing Li; Qing Huang; Qing Huang; et al. (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a common chronic, autoimmune-mediated inflammatory and neurodegenerative disease of the central nervous system. The treatment of MS has enormous progress with disease-modifying drugs, but the complexity of the disease course and the clinical symptoms of MS requires personalized treatment and disease management, including non-pharmacological treatment. Transcranial magnetic stimulation (TMS) is a painless and non-invasive brain stimulation technique, which has been widely used in neurological diseases. In this review, we mainly focus on the progress of physiological assessment and treatment of TMS in MS.